Konsep dasar dan latar belakang Pendidikan Multikultural - Dedi Junaedi; Sahliah (Indonesian Journal of Islamic Religious Education, 2023)
This article explains the basic concepts and background of multicultural education. This article aims to examine the concept and background of multicultural education. Writing this article using a qualitative method with the type of research library research. The data collection technique in writing this article is to collect various sources on the subject and then study it more deeply. The data analysis used is Content Analysis. This study found that 1) Multicultural education is a conscious and planned process of providing services to students to provide understanding, appreciation, and assessment without discriminating between individual differences. 2) The background of multicultural education, namely the second world war and increasing diversity in western countries, that it also resulted from political, social, economic, and intellectual interests